Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

The average daily temperature, [tex]\( t \)[/tex], in degrees Fahrenheit for a city is modeled by the equation
[tex]\[ t = 35 \cos \left( \frac{\pi}{6}(m+3) \right) + 55, \][/tex]
where [tex]\( m = 0 \)[/tex] represents January 1, [tex]\( m = 2 \)[/tex] represents March 1, and so on. Which equation also models this situation?

A. [tex]\( t = -35 \sin \left( \frac{\pi}{6} m \right) + 55 \)[/tex]
B. [tex]\( t = -35 \sin \left( \frac{\pi}{6}(m+3) \right) + 55 \)[/tex]
C. [tex]\( t = 35 \sin \left( \frac{\pi}{6} m \right) + 55 \)[/tex]
D. [tex]\( t = 35 \sin \left( \frac{\pi}{6}(m+3) \right) + 55 \)[/tex]


Sagot :

To determine which equation also models the temperature [tex]\( t \)[/tex] as a function of months [tex]\( m \)[/tex], let's start with the given function:

[tex]\[ t = 35 \cos \left(\frac{\pi}{6}(m+3)\right) + 55 \][/tex]

We need to find an equivalent equation using the sine function. Let's rewrite the cosine function in terms of the sine function using trigonometric identities. We can use the identity:

[tex]\[ \cos(x) = \sin\left( \frac{\pi}{2} - x \right) \][/tex]

First, let's set [tex]\( x = \frac{\pi}{6}(m + 3) \)[/tex]:

[tex]\[ \cos\left(\frac{\pi}{6}(m + 3)\right) \][/tex]

Using the identity, we substitute [tex]\( x \)[/tex]:

[tex]\[ \cos\left(\frac{\pi}{6}(m + 3)\right) = \sin\left(\frac{\pi}{2} - \frac{\pi}{6}(m+3)\right) \][/tex]

Now, simplify the argument of the sine function:

[tex]\[ \frac{\pi}{2} - \frac{\pi}{6}(m + 3) = \frac{\pi}{2} - \frac{\pi}{6}m - \frac{\pi}{6} \cdot 3 \][/tex]
[tex]\[ = \frac{\pi}{2} - \frac{\pi}{6}m - \frac{\pi}{2} \][/tex]
[tex]\[ = -\frac{\pi}{6}m \][/tex]

Thus:

[tex]\[ \cos\left(\frac{\pi}{6}(m + 3)\right) = \sin\left(-\frac{\pi}{6}m\right) \][/tex]

Next, we use the odd property of the sine function, which states:

[tex]\[ \sin(-x) = -\sin(x) \][/tex]

So:

[tex]\[ \sin\left(-\frac{\pi}{6}m\right) = -\sin\left(\frac{\pi}{6}m\right) \][/tex]

Substituting this back into the original equation:

[tex]\[ t = 35 \cos\left(\frac{\pi}{6}(m + 3)\right) + 55 \][/tex]
[tex]\[ = 35 \left[\sin\left(-\frac{\pi}{6}m\right)\right] + 55 \][/tex]
[tex]\[ = 35 \left[-\sin\left(\frac{\pi}{6}m\right)\right] + 55 \][/tex]
[tex]\[ = -35 \sin\left(\frac{\pi}{6}m\right) + 55 \][/tex]

Thus, the equivalent equation that also models the average daily temperature [tex]\( t \)[/tex] as a function of months [tex]\( m \)[/tex] is:

[tex]\[ t = -35 \sin\left(\frac{\pi}{6}m\right) + 55 \][/tex]

So, the correct answer is:

[tex]\[ t = -35 \sin\left(\frac{\pi}{6}m\right) + 55 \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.